Senataxin, the ortholog of a yeast RNA helicase, is mutant in ataxia-ocular apraxia 2. - Moreira, M; Klur, S; Watanabe, M; Németh, A; Le Ber, I; Moniz, J; Tranchant, C; Aubourg, P; Tazir, M; Schöls, L; Pandolfo, M; Schulz, J; et al. (2004)
Ataxia-ocular apraxia 2 (AOA2) was recently identified as a new autosomal recessive ataxia. We have now identified causative mutations in 15 families, which allows us to clinically define this entity by onset between 10 and 22 years, cerebellar atrophy, axonal sensorimotor neuropathy, oculomotor apraxia and elevated alpha-fetoprotein (AFP). Ten of the fifteen mutations cause premature termination of a large DEAxQ-box helicase, the human ortholog of yeast Sen1p, involved in RNA maturation and termination.